Influence of agrotechnical ways on microbiocoenosis of the grey forest soil - Малиновська, І. М.; Ткаченко, М. А.; Сачок, В. Г.; Скуміна, М. О. (Problems of Environmental Biotechnology, 2014)
Researched influence of agrotechnical ways: mineral fertilizer, lime application, a plowing of biomass of sideralny culture and a predecessor in a crop rotation on microbiological processes in a root zone of winter wheat. It is established that lime application leads to increase in quantity of microorganisms of the primary ekologo-trophic groups, decrease in activity of a mineralization of a humus: in the absence of mineral fertilizer – for 8,77 %, against mineral fertilizer – for 10,6 %, for introduction exogenous organic substance – for 28,6 %; to reduction of activity of an expenditure of organic substance of the soil: in the absence of mineral fertilizer for 28,5%, against mineral fertilizer – for 25,3 %, for introduction exogenous organic substance – for 47,9 %; to decrease in intensity of processes of a mineralization of compounds of nitrogen, especially, for introduction exogenous organic substance on a single dose of fertilizers – by 1,90 times, in 1,5 doses – 2,61, for a double dose – by 3,75 times. The increase in a dose of mineral fertilizers also leads to delay of a mineralization of humus, general organic substance of the soil and compounds of nitrogen. Plowing of biomass of sideralny culture and collateral products of a predecessor in a crop rotation the agrocoenosis about what witnesses growth of number of an azotobacter, decrease in content the micromycetes synthesis of melanin for 12,4 %, reduction of phytotoxicity of the soil by 16,8 % in comparison with average phytotoxicity of the soil of options where exogenous the organic substance isn't brought improves ecological conditions.